Analysis of Co(II) Concentration Using Cyclic Voltammetry Technique - Shynta Ramadhan; Gayatri Citra Dewi (Chemistry and Materials, 2022)
Cobalt (Co), as one of the toxic and non-biodegradable heavy metals, has polluted most of the waters, which has an impact on human health and biotic components. Currently, the electrochemical method as a fast, accurate, and reliable technique for detecting heavy metals has been widely developed. Therefore, to obtain results with high accuracy, it is necessary to carry out the analysis under conditions suitable for the heavy metal to be analyzed. In this study, several parameters of Co metal content analysis, such as voltage range, scan rate, and pH were examined using the cyclic voltammetry technique. Metal content analysis using atomic absorption spectrometry was also carried out as a comparison. Based on the results of the analysis of Co metal in the waste solution, it shows that the measurement conditions for the analysis of Co(II) metal are each with a voltage range of 0.75 V to -1.5 V, a scan rate of 200 mV/s, and a pH of 7. The detection limit and quantization limit of Co(II) standard solution are 217.06 mg/L and 723.5 mg/L, respectively, with an RSD of 0.9% and a validity value of the correlation coefficient of 0.9992.